Tathbiq Thoriqoh Al-Ghina’ Li Tanmiyati Dawafi’ Tholabah al-Fashli al-Tsamin Atsna’a Ta’lim al-Lughoh al-Arobiyyah fi al-Madrosah al-Mutawassithoh al-Ahliyah “Ruh Al-Jadid” Jombang (April & October, 2024)
Motivation is the path that leads a person to achieve the desired goal. In learning, motivation plays an important role in increasing students' enthusiasm for learning. Therefore, teachers are required to choose methods and learning media that are fun for students so that students are motivated and more enthusiastic in learning The focus of this research: (1) Motivation of 8th graders of SMPIT Ar-Ruhul Jadid Jombang in learning Arabic, (2) Application of the singing method in increasing student motivation in learning Arabic of 8t h graders of SMPIT Ar-Ruhul Jadid Jombang This study used descriptive qualitative method . This study describes students' learning motivation in learning Arabic, how to apply the singing method in increasing motivation to learn Arabic in 8th grade students of SMPIT Ar-Ruhul Jadid Jombang, Arabic learning activities, and supporting factors for Arabic language development. Data obtained through observation, interviews and documentation. Data analysis using data reduction, data presentation and data inference The results obtained are: (1) the motivation of the 8th graders of SMPIT Ar-Ruhul Jadid Jombang who is very extraordinary and diverse in learning Arabic, they have high learning motivation and curiosity to master Arabic, (2) singing method is an effective learning method. The application of the singing method in learning Arabic for 8th grade students of SMPIT Ar-Ruhul Jadid Jombang is very useful for students at the school. With the implementation of the singing method, students are more active and enthusiastic in learning, and make students more confident to perform and speak in Arabic